A method for durian precise fertilization based on improved radial basis neural network algorithm - Tang, Ruipeng; Wei, Sun; Jianxun, Tang; Aridas, Narendra Kumar; Talip, Mohamad Sofian Abu (Frontiers in Plant Science, 2024)
Durian is one of the tropical fruits, which requires soil nutrients in its cultivation. It is important to understand the relationship between the content of critical nutrients, such as nitrogen (N), phosphorus (P) and potassium (K) in the soil and durian yield. How to optimize the fertilization plan is also important to the durian planting. So this study proposes an Improved Radial Basis Neural Network Algorithm (IM-RBNNA) in the durian precision fertilization. It uses the gray wolf algorithm to optimize the weights and thresholds of the RBNNA algorithm, which can improve the prediction accuracy of the RBNNA algorithm for the soil nutrient content and its relationship with the durian yield. It also collects the soil nutrients and historical yield data to builds the IM-RBNNA model and compares with other similar algorithms. The results show that the IM-RBNNA algorithm is better than the other three algorithms in the average relative error, average absolute error and coefficient of determination between the predicted and true values of soil N, K and P fertilizer contents. It also predicts the relationship between soil nutrients and yield, which is closer to the true value. It shows that the IM-RBNNA algorithm can accurately predict the durian soil nutrient content and yield, which is benefited for farmers to make agronomic plans and management strategies. It uses soil nutrient resources efficiently, which reduces the environmental negative impacts. It also ensures that the durian tree can obtain the appropriate amount of nutrients, maximize its growth potential, reduce production costs and increase yields.